On a Bilinear Operator Free Third Order Method on Riemannian Manifolds - Plaza, S (ELSEVIER SCIENCE INC, 2013)
We present a semilocal convergence analysis of a bilinear operator free third order method on Riemannian manifolds. Using a combination of generalized Lipschitz and center-Lipschitz conditions, we provide a convergence analysis which expands the applicability of the method even in the setting of nonlinear equations considered in earlier studies such as (cf. [4,9,38]). © 2012 Elsevier B.V. All rights reserved.